Análise do registro do processo de enfermagem mediado por tecnologia de informação: estudo de caso - Pereira, Raphael Brandão (2014)
The information and communication technologies havebeen increasingly incorporated to nursing practices, to support the use and the record of nursing process, demanding the monitoring of its results achieved and intervenient factors on a continuous basis. The present study had the objective of providing an analysis of record of nursing process supported by communication and information technologies and the intervenient factors intervenient factors in the nurses’ perception. It is a study of a single integrated case, carried out at the neonatal intensive care unit of a university hospital, located at the Midwest region of the country, from January to April 2014. The new technologies consisted of a data collection/nursing development protocol, specific for a neonatal intensive care unit, and the use of support software to the diagnostic steps, health care planning (target, objective and prescription statements), implementation and evaluation. The data collection was held through the application of a questionnaire and data collected from nurses’ records at patients’ medical files. The study integrated unit consisted of seven nurses, who worked in the section before (from September to November 2010) and after (from September to November 2012) the implementation of the communication and information technologies to support the use and record of the nursing process. The level of application of the nursing process (NAPE) was classified from 1 to 5, according to its accuracy. The records number in each stage of the nursing process was calculated for each day of nursing attendance during the study period. The quantitative data was analyzed through descriptive statistics. The nurses’ statements on intervenient factors were analyzed using the Donabedian health assessment model (1984). There was an increase of records units by nursing service delivery days (UR/DAY), during data collection stages from 55.2 UR/DAE to 80.4% UR/DAE, new nursing diagnostic records to 0.3 UR/DAE, of targets and objectives (1.0 UR/DAE), and of nursing evaluation (0.2 UR/DAE). The stage of nursing prescription had a decrease from 2.1 UR/DAE to 1.9% UR/DAE and the implementation from 4.4 UR/DAE to 3.1 UR/DAE. It was possible to identify the record of more stages of the nursing process if compared with the period before the new technologies started to be used. Nevertheless this increase was not so significant. Among the intervenient factors, time availability was considered enough for the nursing process (PE) application, and besides that, the record remained incipient. Nurses that reported receiving satisfactory or very satisfactory training on the PE or on the use of new communication and information technologies, also reported more stages of the PE. Considering the strategic relevance of adequate record of nursing service delivery and of the legal and ethical requirement of the nursing process, even small improvements may be relevant. However, in general, it is possible to conclude that the insertion of new technologies associated to the training process did not have a significant impact in the stages of the nursing process at the context of the study.